A study on fetomaternal outcome in premature rupture of membranes - Mondal, Arnab; Kanungo, Sanhita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Premature rupture of membranes (PROM) is a common obstetric complication. This condition may lead to maternal complications like puerperal hemorrhage, puerperal sepsis, chorioamnionitis, maternal death etc. due to increased risk of infections and operative interventions. It may also lead to neonatal complications like prematurity, respiratory distress syndrome (RDS), sepsis, low birth weight (LBW) and perinatal death. The aim of the study was to find out whether certain maternal and neonatal complications were significantly higher in PROM cases than controls. Methods: In the present study, the definition of PROM adopted is – rupture of fetal membranes before the onset of true labor pain. The lower limit of gestational age was taken to be 28 weeks. Diagnosis of PROM was mainly clinical. Culture sensitivity test of amniotic fluid was done. The mother was observed throughout labor and postnatal period till discharge and any complications were noted. The baby was also observed from birth till discharge and any complications and interventions were noted. Data obtained was analysed by appropriate statistical methods to obtain results and reach the conclusion. Results: The results of the study showed that the incidence of puerperal hemorrhage, LBW babies, prematurity, maternal morbidities, chorioamnionitis, perinatal mortality and neonatal morbidities were significantly higher in PROM cases. These results corroborated with the findings of other researchers most of the time. Conclusions: It was concluded that individualized management of PROM cases depending on the gestational age and risk of complications is the best way to achieve a good fetomaternal outcome in such cases.